RBEDH: A Decentralized Role-Based Event Driven Hybrid Framework for Smart Contracts - Eashwar Sivakumar; Kiran Jot Singh; Paras Chawla; Geetha Ganesan (IEEE Access)
The complex nature of smart contracts necessities the development of a novel adaptable framework. As blockchain technology continues to expand into diverse fields, the demand for secure, efficient, and transparent systems becomes increasingly critical. RBEDH is the integration of Role Based Access Control (RBAC), Event Driven Architecture (EDA) and Hybrid Functionalities. The framework is applied to the scholarly publishing sector, where academic integrity, transparency, and reliability are crucial for ensuring the credibility and trustworthiness of published research. The smart contracts are executed between authors, reviewers and publishers. Functionality test was conducted using Ganache, Ropsten, and Ethereum Mainnet. These evaluations confirmed the consistency and effectiveness of contract deployment. Vulnerabilities such as re-entrancy, integer overflow/underflow, unauthorized access were tested using Securify, Mythril, Smartcheck and Oynete. It is found that the system is secure and it not susceptible to any of the above vulnerability. Further timestamp dependency was tested through Manticore, Slither and Echidna and the test results indicate the absence of vulnerability. Scalability and performance analysis results proves that the proposed framework is better on the basis of average energy consumption, latency and memory requirement when compared with the existing literature.